2022
DOI: 10.1002/fee.2454
|View full text |Cite
|
Sign up to set email alerts
|

Small artificial impoundments have big implications for hydrology and freshwater biodiversity

Abstract: Headwater streams are critical for freshwater ecosystems. Global and continental studies consistently show major dams as dominant sources of hydrological stress threatening biodiversity in the world’s major rivers, but cumulative impacts from small artificial impoundments (SAIs) concentrated in headwater streams have rarely been acknowledged. Using the Murray Darling River basin (Australia) and the Arkansas River basin (US) as case studies, we examined the hydrological impacts of SAIs. The extent of their infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Climate‐induced droughts and low flow events can cause the loss of spatial connectivity, and may also increase competition and predation from lentic species as swift running waters becomes slow‐flowing (Jonsson and Jonsson 2009, Hasegawa and Yamamoto 2010). A major threat to trout abundance in a climate change scenario are dams for hydropower production and small artificial impoundments, which are the main drivers of water stress and habitat fragmentation (Arthington et al 2016, Sabater et al 2018, Morden et al 2022). In a recent study, we found that trout populations were more negatively affected by intense river regulation from hydropower dams in warmer regions compared to populations in colder regions (Donadi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Climate‐induced droughts and low flow events can cause the loss of spatial connectivity, and may also increase competition and predation from lentic species as swift running waters becomes slow‐flowing (Jonsson and Jonsson 2009, Hasegawa and Yamamoto 2010). A major threat to trout abundance in a climate change scenario are dams for hydropower production and small artificial impoundments, which are the main drivers of water stress and habitat fragmentation (Arthington et al 2016, Sabater et al 2018, Morden et al 2022). In a recent study, we found that trout populations were more negatively affected by intense river regulation from hydropower dams in warmer regions compared to populations in colder regions (Donadi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lessons of past projects to restore river conditions also could be applied to current design and practice for activities that continue to alter rivers. For instance, we have been in a global dam‐building era (Couto & Olden, 2018; Morden et al., 2022), so understanding the benefits of improved connectivity from restoration outcomes may be a persuasive incentive to incorporate fish passage (ways) in original dam constructions. The capability of making broad syntheses to better guide future restoration efforts would be facilitated by including improved data reporting, describing context‐dependent factors within catchments that affect ecological outcomes, and promoting restoration project results in publicly accessible online databases or publications.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be a conservative estimate given that many small impoundments constructed on private lands are not listed on the lake registry. Artificial impoundments considerably alter hydrology in both small and large streams (Ward & Stanford, 1995; Morden et al, 2022). These novel environments also create habitats where lentic‐dwelling species can become established and exert propagule pressure on connected streams (Gido & Brown, 1999; Woodford et al, 2013).…”
Section: Discussionmentioning
confidence: 99%